The Application Of The Pictures In Comprehending Reading Text To The Eighth Grade Students Of SMPN 2 Gelumbang - Sherly Marliasari (Journal of Language Education (JoLE), 2018)
The objective of this study is to find out whether or not it is effective to use pictures in comprehending reading text to the eighth grade students of SMPN 2 Gelumbang. The methodology of the research used quasi experimental method. The populations of this study consisted of three classes of eighth grade students. The result of t-test formula in pre-test of experimental group and control group was 1.314 and the result of independent t-test formula in posttest of experimental group and control group was 5.151. The critical value in the t-table is 2.000, so that 5.151 > 2.000. It means that (Ho) was rejected and the alternative hypothesis (Ha) was accepted, because tobt ttab where tobt = 5.151 and ttab= 2.000. It can be concluded, using pictures in comprehending reading text to the eighth grade students of SMPN 2 Gelumbang was effective.